(untitled) (SAARC Journal of Agriculture, 2018)
The concept of farm to consumer direct marketing has been popularly known to create opportunities for farmer-consumer relationship and enhance the sustainability of the local farming business. The objective of the present study was to predict the consumers’ willingness to pay for fresh produce in the direct marketing outlets and agritourism activities. An Internet survey relating to direct marketing and agritourism was conducted to understand the characteristics of consumers. A total of 1,134 participants completed the survey from Delaware, New Jersey, and Pennsylvania. Based on their responses, an ordered probit model was developed at a low premium (1-5 percent), medium premium (6-10 percent) and high premium (11percent and above) to predict respondents’ willingness to pay a premium for produce sold at direct marketing outlets. The estimated results show that consumers’ willingness to pay more to help preserve farmland or local business is highly significant. However, we discovered an inverse relationship for the Mid-Atlantic fresh greens shoppers. On average, as the travel distance increases, the likelihood of paying a higher premium decrease based on each additional mile they travel. The results of the ordered probit model will help all relevant stakeholders from the Mid-Atlantic States to promote direct marketing and agritourism industry in the region and enhance their knowledge of the industry. SAARC J. Agri., 15(2): 19-30 (2017)